Metodología en operaciones de cementación priMaría y forzada utilizando nuevas tecnologías - Herzog Zambrano, Pierre Andrés (2011)
The purpose of this work consists in the analysis of an operative alternative that is possible for the cementing of the CHS-3D well, the one that is in Yuca field We determine the volume of the cement for the lead cement and tail cement, that is required the sections of the program, we compare the design of this proposal with the actual model, and we determined that in each section the excess of the cement vary significantly in the first two sections we will cement up to the surface designing two cement and in the liner section we will cement with only one cement. The results will be analyzed in a comparative form. Based on our proposal is applicable. It is recommended that to avoid the operational problems that could occur during the development of this work, we must consider that the annular must be with no contaminants and that the cement is composition, volume and time must be the adequate.